The Failure of the United Nations Security Council in Creating the Framework Conditions for Mediation in the Russia-Ukraine Crisis (The Strategic Review for Southern Africa, 2022)
This article argues that during the 2022 Russian Federation invasion of Ukraine, the United Nations Security Council (UNSC) failed to create the framework conditions to facilitate the mediation of the crisis due to the systemic constraints created by the veto powers of the Permanent Five (P5) members of the Council. Specifically, the institutional gap created by a dysfunctional UNSC, efforts to mediate ongoing and future crises in which one or more members of the P5 are involved are confronted by the same systemic failure. Given the reality of the UNSC’s paralysis and the indefinite postponement of UN reform, this article argues for the need for radical transformation of the international system and the articulation of a new global democratic architecture, which includes a new global infrastructure for mediation. The article concludes with a discussion of how a UN Charter review process can lay the foundation for the establishment of this new global democratic dispensation, which includes a new global infrastructure for mediation.
Keywords: Russia; Ukraine; Mediation; United Nations Security Council (UNSC); War